Sistem Informasi Geografis Pemetaan Museum Di Bali Berbasis Android - Nyoman Renata; Nyoman Yudi Anggara Wijaya; Ida Bagus Kresna Sudiatmika (Universitas Merdeka Malang, 2020)
A museum is an institution that maintains and exhibits a collection of objects of cultural and scientific value for research, educational and entertainment purposes. The purpose of the creation of the museum is a means of educational tourism, interesting and informative for society. Thus, the museum plays a very important role because the existence of the museum will provide a broad understanding for the community. But here the problem is the lack of comprehensive information about Bali's museums, especially museums that are rarely visited by tourists. So that people only know about famous museums. With this Android-based Bali Museum Map Information System, it can help both the public and tourists to find information about museums in Bali, ranging from well-known or frequently visited museums to rarely visited museums. The existence of this information system also helps to find information about the history of the museum, its location and the history of the existing collections in each museum. The method used in this study uses the prototype method, where every process that we have tested the user to what we are doing, met the user's expectations.